Enrichment of high affinity subclasses and glycoforms from serum‐derived IgG using FcγRs as affinity ligands. Issue 5 (1st February 2018) - Boesch, Austin W.; Kappel, James H.; Mahan, Alison E.; Chu, Thach H.; Crowley, Andrew R.; Osei‐Owusu, Nana Y.; Alter, Galit; Ackerman, Margaret E.
Abstract: As antibodies continue to gain predominance in drug discovery and development pipelines, efforts to control and optimize their activity in vivo have matured to incorporate sophisticated abilities to manipulate engagement of specific Fc binding partners. Such efforts to promote diverse functional outcomes include modulating IgG‐Fc affinity for FcγRs to alternatively potentiate or reduce effector functions, such as antibody‐dependent cellular cytotoxicity and phagocytosis. While a number of natural and engineered Fc features capable of eliciting variable effector functions have been demonstrated in vitro and in vivo, elucidation of these important functional relationships has taken significant effort through use of diverse genetic, cellular and enzymatic techniques. As an orthogonal approach, we demonstrate use of FcγR as chromatographic affinity ligands to enrich and therefore simultaneously identify favored binding species from a complex mixture of serum‐derived pooled polycloncal human IgG, a load material that contains the natural repertoire of Fc variants and post‐translational modifications. The FcγR‐enriched IgG was characterized for subclass and glycoform composition and the impact of this bioseparation step on antibody activity was measured in cell‐based effector function assays including Natural Killer cell activation and monocyte phagocytosis. This work demonstrates a tractable means to rapidly distinguish complex functional relationships between two or more interacting biological agents by leveraging affinity chromatography followed by secondary analysis with high‐resolution biophysical and functional assays and emphasizes a platform capable of surveying diverse natural post‐translational modifications that may not be easily produced with high purity or easily accessible with recombinant expression techniques. Abstract : Boesch and coworkers demonstrate the use the of FcgRs as affinity ligands to enrich natural human IgG glycoforms and subclass variants. Structure‐function relationships of these enriched fractions were further characterized using cell based assays such as Natural Killer cell degranulation and Monocyte mediated phagocytosis. This work demonstrates a tractable means to rapidly distinguish complex functional relationships between two or more interacting biological agents by leveraging affinity chromatography followed by secondary analysis with high‐resolution biophysical and functional assays.